A secreted protein is an endogenous chemorepellant in Dictyostelium discoideum - Phillips, Jonathan E. (National Academy of Sciences, 2012)
Chemorepellants may play multiple roles in physiological and pathological processes. However, few endogenous chemorepellants have been identified, and how they function is unclear. We found that the autocrine signal AprA, which is produced by growing Dictyostelium discoideum cells and inhibits their proliferation, also functions as a chemorepellant. Wild-type cells at the edge of a colony show directed movement outward from the colony, whereas cells lacking AprA do not. Cells show directed movement away from a source of recombinant AprA and dialyzed conditioned media from wild-type cells, but not dialyzed conditioned media from aprA(−) cells. The secreted protein CfaD, the G protein Gα8, and the kinase QkgA are necessary for the chemorepellant activity of AprA as well as its proliferation-inhibiting activity, whereas the putative transcription factor BzpN is dispensable for the chemorepellant activity of AprA but necessary for inhibition of proliferation. Phospholipase C and PI3 kinases 1 and 2, which are necessary for the activity of at least one other chemorepellant in Dictyostelium, are not necessary for recombinant AprA chemorepellant activity. Starved cells are not repelled by recombinant AprA, suggesting that aggregation-phase cells are not sensitive to the chemorepellant effect. Cell tracking indicates that AprA affects the directional bias of cell movement, but not cell velocity or the persistence of cell movement. Together, our data indicate that the endogenous signal AprA acts as an autocrine chemorepellant for Dictyostelium cells.